2011
DOI: 10.1042/bj20101437
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-dependent compartmentalization of PPIP5K1, a kinase with a cryptic polyphosphoinositide binding domain

Abstract: The inositol pyrophosphates are multifunctional signalling molecules. One of the families of enzymes that synthesize the inositol pyrophosphates are the Vip1/PPIP5Ks (PP-InsP5 kinases). The kinase domains in Vip1/PPIP5Ks have been mapped to their N-terminus. Each of these proteins also possess a phosphatase-like domain of unknown significance. In the present study, we show that this phosphatase-like domain is not catalytically active. Instead, by using SPR (surface plasmon resonance) to study protein binding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 54 publications
3
76
2
Order By: Relevance
“…Generation of inositol pyrophosphates has been shown for the budding yeast and human Vip1 family members [43][45], [48]. In this work we have extended the analysis to two further fungal Vip1-like proteins: the S. pombe Asp1 and the A. nidulans VlpA.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Generation of inositol pyrophosphates has been shown for the budding yeast and human Vip1 family members [43][45], [48]. In this work we have extended the analysis to two further fungal Vip1-like proteins: the S. pombe Asp1 and the A. nidulans VlpA.…”
Section: Discussionmentioning
confidence: 91%
“…A recent publication has shown that the phosphatase-like domains of the human Vip1 members are catalytically inactive. Instead the authors show that this domain plays a role in inositol lipid binding [48]. On the other hand, a comparison of the amounts of inositol pyrophosphates generated by human and the S. cerevisiae full-length Vip1 proteins versus N-terminal kinase-domain-only-variants, showed that the latter variants exhibited more specific activity [43], [45].…”
Section: Discussionmentioning
confidence: 96%
“…A proteomics prediction that PPIP5K1 can be found in the nucleus [100] is contradicted by the finding that it is excluded from the nucleus of NIH 3T3 and HEK293 cells [97,99]. Phosphorylations of PPIP5K1 at Ser475, Tyr730, Ser944 and Ser1152 have been reported [101103].…”
Section: Inositol Hexakisphosphate and Diphosphoinositol-pentakisphosmentioning
confidence: 99%
“…75 Both the PPIP5K isoforms possess a lipid inositide binding domain distinct from their kinase domains, and agonist-stimulated production of PI(3,4,5)P 3 can lead to translocation of PPIP5K1 from the cytoplasm to the plasma membrane. 41,76 As suggested by the ubiquitous expression and localisation of the kinases responsible for their synthesis, PP-IPs have been shown to participate in a myriad functions in many different tissues and subcellular compartments. This section describes several functions of these small molecules in different locations within a cell (Fig.…”
Section: The Functions Of Pp-ips In Differentmentioning
confidence: 99%